The phagocytosis activity of isoeugenol-ester compound on Mus musculus macrophage cell - AWIK PUJI DYAH NURHAYATI; MARDI SANTOSO; EDWIN SETIAWAN; DEAVINA THALITA RACHMA (Smujo International, 2019)
Abstract. Authors. 2019. The activity phagocytosis of isoeugenol-ester compound on Mus musculus macrophage cell. Nusantara Bioscience 11: 117-122. Chemotherapy is drugs therapy for cancer. However, chemotherapy could damage normal cells and decrease immune system. For this reason, it is necessary to find immunostimulant compound that is able to increase immune system. Isoeugenol-ester is unnatural compound that has been tested for its cytotoxicity against cancer cell and showed positive result. Nevertheless, ability of Isoeugenol-ester for inducing phagocytosis is still unknown. Therefore, bioassays study using in vitro phagocytosis were performed. Latex beads methods using antigen model in 5 isoeugenol-ester concentration series: 6, 25; 12, 5; 25; 50 and 100 ?g/mL were tested to Mus musculus peritoneal macrophage cell. The optimum concentration of Isoeugenol-ester compounds in inducing phagocytosis activity of M. musculus macrophage cell was 12.5 ?g/mL.